Development of accurate temperature regulation culture system with metallic culture vessel demonstrates different thermal cytotoxicity in cancer and normal cells - Chikahiro Imashiro (Nature Portfolio, 2021)
Abstract Hyperthermia has been studied as a noninvasive cancer treatment. Cancer cells show stronger thermal cytotoxicity than normal cells, which is exploited in hyperthermia. However, the absence of methods evaluating the thermal cytotoxicity in cells prevents the development of hyperthermia. To investigate the thermal cytotoxicity, culture temperature should be regulated. We, thus, developed a culture system regulating culture temperature immediately and accurately by employing metallic culture vessels. Michigan Cancer Foundation-7 cells and normal human dermal fibroblasts were used for models of cancer and normal cells. The findings showed cancer cells showed stronger thermal cytotoxicity than normal cells, which is quantitatively different from previous reports. This difference might be due to regulated culture temperature. The thermal stimulus condition (43 °C/30 min) was, further, focused for assays. The mRNA expression involving apoptosis changed dramatically in cancer cells, indicating the strong apoptotic trend. In contrast, the mRNA expression of heat shock protein (HSP) of normal cells upon the thermal stimulus was stronger than cancer cells. Furthermore, exclusively in normal cells, HSP localization to nucleus was confirmed. These movement of HSP confer thermotolerance to cells, which is consistent with the different thermal cytotoxicity between cancer and normal cells. In summary, our developed system can be used to develop hyperthermia treatment.